Reversible P2Y12 inhibitor versus irreversible P2Y12 inhibitor in ACS patients undergoing PCI (the acute coronary syndrome israeli survey (ACSIS). (14th October 2021) - Eliaz, R; Mengesha, B; Ovdat, T; Iakobishvili, Z; Hasdai, D; Kheifets, M; Klempfner, R; Beigel, R; Kalmanovich, E; Alcalai, R; Levi, A; ,
Abstract: Introduction: Based on data from randomized controlled trials, both American and European guidelines recommend treating acute coronary syndrome (ACS) patients with second generation P2Y12 inhibitors.1, 2 Direct head-to-head comparison of these agents was scarce until the recent publication of the ISAR-REACT-5 study which demonstrated the superiority of the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) over the reversible P2Y12 inhibitor in terms of 1-year composite of death, myocardial infarction (MI), and stroke.3, 4, 5 Given the unexpected outcomes of this trial, we sought to perform a comparison of ticagrelor and prasugrel in real-life ACS patients. Purpose: To compare the outcomes of ACS (acute coronary syndrome) patients undergoing in-hospital PCI (percutaneous coronary intervention) treated with the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) versus the reversible P2Y12 inhibitor. Methods: ACSIS (Acute Coronary Syndrome in Israel) is a national ACS snapshot survey conducted in all 25 cardiology departments in Israel since 2000 over a two-month period, every two to three years. Both the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) and the reversible P2Y12 inhibitor were commercially introduced in Israel in 2010. We therefore considered patients enrolled in ACSIS surveys 2010–2018 for the present analysis. Results: Among 7, 233 patients enrolled to the ACSIS (Acute Coronary Syndrome in Israel) registry between 2010 and 2018, we identified 1133 eligible patients treated with the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) and 825 with the reversible P2Y12 inhibitor. In hospital complication rates, including rates of stent thrombosis, were roughly similar between groups. Compared to the reversible P2Y12 inhibitor, the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) was associated with lower 1-year death in ST-elevation myocardial infarction (STEMI) patient compared to non-ST-elevation ACS (NSTE-ACS) patients (p for interaction 0.03). In propensity score matched STEMI patients (502 receiving the Irreversible thienopyridine type P2Y12 inhibitor (prodrug), 251 the reversible P2Y12 inhibitor) 30-day re-hospitalization rate (p<0.05), 30-day MACE (the composite of death, MI, stroke, urgent revascularization; p=0.006), and 1-year mortality rates (p=0.08) were higher in the the reversible P2Y12 inhibitor group compared to the the Irreversible thienopyridine type P2Y12 inhibitor (prodrug) group; In NSTE-ACS patients, outcomes were not impacted by drug choice. Conclusion: The Irreversible thienopyridine type P2Y12 inhibitor (prodrug) was more effective than the reversible P2Y12 inhibitor in STEMI patients, but not in NSTE-ACS patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): the Israeli working group on acute cardiac care of the Israel heart society